Problematyka rezerwy na szkody o rozmiarach katastrofalnych w gospodarce finansowej zakładów ubezpieczeń - Pastusiak, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Main goal of this article it is presentation of techniques creating catastrophic reserves in insurance company. Insurance process is join with demands pays for losses where owner or victims had insurance policy. But some of this losses are very big and have great meaning for insurance company.Reserves for catastrophic losses have special treatment in financial politics of insurance company. First at all very complicated is find true value of this reserves. New actuarial methods no guaranty his reality. Question is: what are consequences take to low or to high catastrophic reserves? To low reserves are dangerous for insurer because they not to cover payments for losses and cause bankruptcy. Reserves to high cause limitation net gain and lowering dividend and of course tax income. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 100-111